GROUP ENGAGEMENT BASED ON SOCIAL EXCHANGE THEORY: ANTECEDENTS AND CONSEQUENCES - Danang Sunyoto; Heru Kurnianto Tjahjono; Zaenal Mustafa El Qodric; Wisnu Prajogo; Syamsul Hadi (Journal of Leadership in Organizations, 2021)
Objectives - In recent years studies on organizational engagement have increasingly been carried out to find out further, and more broadly, both antecedent variables and consequent variables, specifically involving individuals as research objects, and there are only a few studies involving groups as research objects. Therefore, this study aims to examine the antecedent model and the consequences of group attachment based on Social Exchange Theory. Design/Methodology/Approach - The population of this research is 113 social sciences study programs in private universities and college, and there are 105 study programs qualify as data. While the object of group research consists of heads and secretaries of the department. The research model uses a census model. Antecedents include perceptions of organizational support, distributive justice, and the consequences of group engagement, namely group performance. Findings - The results show that the perception of organizational support directly predicted group engagement and group performance, the distributive justice predicted group engagement but not group performance, and the group engagement predicted group performance. Indirectly, it was found that group attachment was significant as a mediator of the effect of perceived organizational support on group performance, and the effect of distributive justice on group performance. Originality - There are still a few studies on group engagement as a mediator and predictor of antecedents and their consequences using group data objects. Therefore, this study offers not only using group data but also providing a wider range of antecedent variables and their consequences based on social exchange theory.